Effect of sintering temperature on crystal structure and physical properties of the Mg0,92Zn0,05C0,03 Alloy - Budiarto Budiarto; Susilo Susilo (Jurnal POLIMESIN, 2023)
The effect of sintering temperature on the crystal structure and physical properties of the Mg0,92Zn0,05C0,03 alloy has been studied. Magnesium-based alloys are one of the alloys that have been used in industry, the health sector, and as biodegradable materials and biomaterials. The aim of this study was to determine the effect of temperature and sintering holding time on crystal size, dislocation density, microlattice strain, and yield strength, porosity and density of Mg0,92Zn0,05C0,03 alloy. The results of testing the crystal structure of the alloy Mg0,92Zn0,05C0,03 with an X-ray diffractometer showed several diffraction peaks consisting of the main phase α–Mg and a small part of the MgZn phase. Testing of Mg0,92Zn0,05C0,03 alloy after sintering with variations in temperature and 90 minutes holding time for crystal size showed that the higher the sintering temperature (425 0C to 575 0C) the crystal size value decreased significantly from 82.36 nm to 18.75 nm, and the dislocation density increased from 0.113 to 0.868 lines/mm2. For micro strain decreased from 0.015 to 0.0087. However, in the very small porosity test, the increase was from 29.8% to 31.9%. As well as for density (1.8 gr/cm3) and yield strength (274 MPa) there was no significant decrease of around 1.4%, but the synthesized Mg0,92Zn0,05C0,03 alloy fulfilled as a bone implant bio material.hhThe effect of sintering temperature on the crystal structure and physical properties of the Mg0,92Zn0,05C0,03 alloy has been studied. Magnesium-based alloys are one of the alloys that have been used in industry, the health sector, and as biodegradable materials and biomaterials. The aim of this study was to determine the effect of temperature and sintering holding time on crystal size, dislocation density, microlattice strain, and yield strength, porosity and density of Mg0,92Zn0,05C0,03 alloy. The results of testing the crystal structure of the alloy Mg0,92Zn0,05C0,03 with an X-ray diffractometer showed several diffraction peaks consisting of the main phase α–Mg and a small part of the MgZn phase. Testing of Mg0,92Zn0,05C0,03 alloy after sintering with variations in temperature and 90 minutes holding time for crystal size showed that the higher the sintering temperature (425 0C to 575 0C) the crystal size value decreased significantly from 82.36 nm to 18.75 nm, and the dislocation density increased from 0.113 to 0.868 lines/mm2. For micro strain decreased from 0.015 to 0.0087. However, in the very small porosity test, the increase was from 29.8% to 31.9%. As well as for density (1.8 gr/cm3) and yield strength (274 MPa) there was no significant decrease of around 1.4%, but the synthesized Mg0,92Zn0,05C0,03 alloy fulfilled as a bone implant bio material.